Peningkatan Hasil Belajar Siswa pada Materi Aritmetika Sosial Melalui Pembelajaran Berdiferensiasi - Fice Femmy Rompis (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to improve the mathematics learning outcomes of grade 7 students in Social Arithmetic material at Leilem Christian Junior High School, Sonder District, odd semester of the 2020/2021 Academic Year by using a differentiated learning approach. This research, including classroom action research, was conducted in two cycles and each cycle was held in two meetings. The subjects in this study were 7-grade students consisting of 9 boys and 12 girls. The data collection technique used in this study was in the form of student observation, teacher observation, and learning achievement tests, then the data obtained were analyzed descriptively. The results showed that there was an increase in teacher activity in learning activities in the first cycle an average of 80.65% and an average of 93.18% in the second cycle. Furthermore, in student activity, there was also an increase in learning activities in the first cycle an average of 77.28%, and in the second cycle an average of 90.91%. As for the student learning outcomes test, it was found that there was an increase from cycle I of 76.19% to 90.48% in cycle II. It can be concluded that differentiated learning can improve student learning outcomes.